Integrating Play-Based Learning in Early Childhood Physical Education: Benefits and Challenges - Zhang Guohui,; Guo Xiujin, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The integration of play-based learning (PBL) into early childhood education (ECE) is gaining increasing recognition due to its potential to enhance children's cognitive, physical, emotional, and social development. This study examines the benefits and challenges associated with incorporating PBL into early childhood physical education (ECPE) across both public and private ECE settings. The study was conducted across 27 ECE facilities, involving 46 instructors and 328 children. Data was analysed using SPSS 23.0 and Mplus 8.0 to perform descriptive statistics and reliability testing. Exploratory Factor Analysis (EFA) was employed to identify the benefits of PBL, while Confirmatory Factor Analysis (CFA) was used to validate its components. A coefficient correlation matrix analysis was conducted to assess the relationships between the beneficial and challenging factors associated with PBL implementation in ECPE. Independent t-tests evaluated the impact of teachers' activities, PBL educational strategies, and curriculum preparation on holistic child development. Multiple regression analysis was applied to explore the interrelationships and significant effects of various benefit and challenge factors on PBL outcomes. The benefits of PBL in ECPE were assessed using fit indices, including χ², TLI, CFI, RMSEA, and SRMR, with SRMR values below 0.08 indicating well-fitting factors. The study highlights that PBL significantly enhances children's socio-emotional, physical, and cognitive development, supporting overall mental and physical health. Both public and private ECE facilities exhibit similar trends, with instructor qualifications and experience playing a crucial role. Active engagement and PBL techniques are key to optimizing developmental outcomes. The study emphasizes the importance of capacity building and tailored curriculum design for the effective implementation of PBL in early childhood physical education, while addressing challenges such as variations in teacher qualifications and experience.